Extracellular electrophysiology on clonal human β-cell spheroids - Puginier, Emilie; Leal-Fischer, Karen; Gaitan, Julien; Lallouet, Marie; Scotti, Pier-Arnaldo; Raoux, Matthieu; Lang, Jochen (Frontiers in Endocrinology, 2024)
Pancreatic islets are important in nutrient homeostasis and improved cellular models of clonal origin may very useful especially in view of relatively scarce primary material. Close 3D contact and coupling between b-cells are a hallmark of physiological function improving signal/noise ratios. Extracellular electrophysiology using micro-electrode arrays (MEA) is technically far more accessible than single cell patch clamp, enables dynamic monitoring of electrical activity in 3D organoids and recorded multicellular slow potentials (SP) provide unbiased insight in cell-cell coupling. We have therefore asked whether 3D spheroids enhance clonal b-cell function such as electrical activity and hormone secretion using human EndoC-bH1, EndoC-bH5 and rodent INS-1 832/13 cells. EndoC-bH1 spheroids exhibited increased signals in terms of SP frequency and especially amplitude as compared to monolayers and even single cell action potentials (AP) were quantifiable. Enhanced electrical signature in spheroids was accompanied by an increase in the glucose stimulated insulin secretion index. EndoC-bH5 monolayers and spheroids gave electrophysiological profiles similar to EndoC-bH1, except for a higher electrical activity at 3 mM glucose, and exhibited moreover a biphasic profile. Again, physiological concentrations of GLP-1 increased AP frequency. Spheroids also exhibited a higher secretion index. INS-1 cells did not form stable spheroids, but overexpression of connexin 36, required for cell-cell coupling, increased glucose responsiveness, dampened basal activity and consequently augmented the stimulation index. In conclusion, spheroid formation enhances physiological function of the human clonal -cell lines and these models may provide surrogates for primary islets in extracellular electrophysiology.